Early infantile presentation of 3-methylcrotonyl CoA carboxylase deficiency: a case report - Chandel, Anuragsingh; Shirsat, Ashwini; Chouhan, Varsha; Bang, Akash (International Journal of Contemporary Pediatrics, 2021)
3-methylcrotonyl CoA carboxylase (3-MCC) deficiency is an inborn error of leucine amino acid metabolism. An isolated enzyme deficiency should be differentiated from biotin metabolism disorder which has all of the four carboxylase deficiencies. With the advent of tandem mass spectrometry (TMS), high number of infants have been diagnosed with 3-MCC deficiency. Most neonates having 3-MCC deficiency appear normal, studies have shown an increased risk of developmental and metabolic abnormalities. Universal newborn screening is not routinely done in India. Many infants with 3-MCC deficiency may be missed at birth and may present with symptoms later in life. We reported a case of four and a half month old male infant with seizures due to 3-MCC deficiency. Very few data on 3-MCC deficiency is available in India and hence this case report.